The Role of Leadership on Organizational Performance Through Paramedic Loyalty in Public Health Centers - Oos Fatimah Rosyati; Linda Chiuman; I Nyoman Ehrich Lister; Chrismis Novalinda Ginting (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study examines the role of leadership in enhancing organizational performance through the mediating effect of paramedic loyalty in public health centers (Puskesmas). Using a quantitative approach, data were collected from paramedics working at various Puskesmas through structured questionnaires. The research model hypothesizes that the role of Puskesmas leaders positively influences both paramedic loyalty and organizational performance, with paramedic loyalty also having a direct positive impact on performance. Furthermore, the study explores the mediating effect of paramedic loyalty on the relationship between leadership and organizational performance. Data analysis was conducted using regression and mediation techniques to test the proposed hypotheses. The findings indicate that effective leadership significantly increases paramedic loyalty, which in turn enhances the overall performance of Puskesmas. Additionally, the results reveal that paramedic loyalty partially mediates the relationship between leadership and organizational performance, emphasizing the importance of fostering loyalty among healthcare staff to achieve optimal organizational outcomes. This research provides valuable insights for public health administrators and policymakers to develop leadership strategies that strengthen staff commitment and improve service delivery in public health centers.